Systematic Review of Research Trends on Creative Thinking Skills in Science Learning (2016-2025) - Astuti, Dini; Harjono, Ahmad; Hadiprayitno, Gito (Current Educational Review, 2025)
Creative thinking skills are one aspect that is part of 21st century skills. However, students' creative thinking skills are still relatively low, so it is very important to improve these skills. This study aims to identify and analyze research trends on creative thinking skills in science learning from 2016-2025. This research method is descriptive and analytical, with data obtained from documents indexed by Google Scholar using Publish or Perish and Dimension.ai. The research procedure uses the PRISMA guidelines and data analysis is carried out using bibliometric analysis assisted by VOSviewer software. The results of the analysis show that the trend of research on creative thinking skills in science learning has increased and decreased during the period 2016-2025. The increase in the number of publications occurred from 2016 to 2021, then decreased in 2022, and increased again from 2023-2024. There are many documents in the form of Chapters, Articles, Edited Books, Monographs, Proceedings, and Preprints that discuss research on creative thinking skills in science learning. Keyword analysis shows that the most frequently occurring terms in this study include Higher order thinking skill as many as 52 times and collaboration as many as 33 times. This trend reflects the growing attention to creative thinking skills in science learning and indicates the need for further efforts to improve research and application in this area